2018
DOI: 10.1214/17-aoas1081
|View full text |Cite
|
Sign up to set email alerts
|

Extreme value modelling of water-related insurance claims

Abstract: snow-melt, and the number of water-related property insurance claims. Weather events which cause severe damages are of general interest, decision makers want to take efficient actions against them while the insurance companies want to set adequate premiums. The modelling is challenging since the underlying dynamics vary across geographical regions due to differences in topology, construction designs and climate. We develop new methodology to improve the existing models which fail to model high numbers of claim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 46 publications
(65 reference statements)
0
12
0
Order By: Relevance
“…Scheel et al (2013) showed that the upper tail of this distribution is exceptionally difficult to model for individual administrative areas (termed municipalities) in Norway. Rohrbeck et al (2018) developed an extremal regression model that shows how the largest numbers of insurance claims per weather event in a municipality can be clearly linked to extreme precipitation in that municipality, and that from such a model, marginalizing over the precipitation gives a good model for the marginal distribution of the number of claims.…”
Section: Weather-related Property Insurance Claims In Norwaymentioning
confidence: 99%
“…Scheel et al (2013) showed that the upper tail of this distribution is exceptionally difficult to model for individual administrative areas (termed municipalities) in Norway. Rohrbeck et al (2018) developed an extremal regression model that shows how the largest numbers of insurance claims per weather event in a municipality can be clearly linked to extreme precipitation in that municipality, and that from such a model, marginalizing over the precipitation gives a good model for the marginal distribution of the number of claims.…”
Section: Weather-related Property Insurance Claims In Norwaymentioning
confidence: 99%
“…A better understanding of the extremes of Y can often be achieved by inferring the conditional extremes of Y given a covariate X. Recent examples include the analysis of high healthcare costs in [49] and large insurance claims in [41]. We focus on the case when Y given X is heavy-tailed (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Coles and Pericchi (2003) demonstrated in a hydrological context the benefits of using the encompassing generalised Pareto model to properly represent uncertainty in the tail shape. Secondly, the exponential distribution does not account for rounding of the data, resulting in biased parameter estimates (Marzocchi et al, 2019;Rohrbeck et al, 2018). Failing to acknowledge this rounding can therefore also cause bias in threshold selection.…”
Section: Introductionmentioning
confidence: 99%